Business Sustainability within the Dynamic Business Climate Change in Indonesia: The Role of Leadership Style and Innovation Culture - Taba, Sattar; Mulyadi, Mohamad; Sharin, Farah Hida
In this day and age, with the process of globalisation still in progress and dynamic change occurring in firms, it is essential to preserve the organisational culture by guiding it in the appropriate direction in order to achieve business sustainability. However, modern organisations require leaders more than ever since their focus is almost exclusively on short-term gains at the expense of any consideration of the future. To effectively navigate the business environment and meet the needs of its customers, leadership is an indispensable instrument. As a result of all of these changes, it is abundantly evident that the leaders who run firms confront major challenges when attempting to adapt to the new conditions. The purpose of this article is to set out to do two things: create a map of the leadership research landscape and make a contribution to the refinement of a conceptual model based on that landscape. Contingency or situational theory has been proposed to support the whole body of study. Any future study topic or scenario variables may be incorporated into the suggested framework. It will be a significant factor in the continued success of Indonesian enterprises.